Photocatalytic activity of CuO and Cu2O nanowires. (February 2016) - Scuderi, V.; Amiard, G.; Boninelli, S.; Scalese, S.; Miritello, M.; Sberna, P.M.; Impellizzeri, G.; Privitera, V.
Abstract: Here we report the photocatalytic efficiency of CuO and Cu2 O nanowires studied by dye degradation in water. The CuO nanowires were synthesized on Cu foils by thermal oxidation. A subsequent thermal annealing induced a controllable phase transformation of the nanowires and the underlying film from CuO to Cu2 O phase. A structural characterization was made by scanning and transmission electron microscopies, energy dispersive x-ray analysis and x-ray diffraction. The photocatalytic performances were evaluated by the degradation of two dyes in water: methylene blue and methyl orange. In particular, CuO nanowires showed a good photocatalytic activity in degrading methyl orange, compared with Cu2 O nanowires. The photocatalytic activity was correlated to the physical-chemical properties of the samples, revealing the detrimental effect of the polycrystalline structure for photocatalytic process.